The Impact of Cooperative Learning Models on Students' Social Skills and Results in Playing Futsal - Eni Desanti; Tite Juliantine (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
The desire of students to participate in sports is very diverse. Starting from students who want to explore the sport of futsal to those students who want to be popular in their school. It is not uncommon for health teachers to use it as a tool for physical education learning, but it is very unfortunate when physical education learning uses a learning model such as training a sport that only emphasizes technical skills. Cooperative learning has several types, one type of cooperative learning that can foster academic competition to be able to compete sportively is the Teams-Games-Tournament (TGT) type cooperative. This type of TGT-type cooperative learning supports student interaction. Students are required to work together, compete and be responsible for achieving group success.  This study aims to:  (1) Know the influence of the TGT-type cooperative learning model on students' social skills, and (2) Know the influence of the TGT-type cooperative learning model on students' futsal playing skills. The research method used is an experimental research method with the research design of One Group Pretest-Postest Design. In this study, the population studied was students who took part in futsal extracurriculars at SMA Negeri 16 Bandung, sampling using the Saturated Sampling technique, which is a technique for determining the sample of all members of the population used as a sample, because the total population is relatively small or less than 30 people, consisting of students who take part in futsal extracurriculars with a total of 20 people.  In the analysis and processing of data, researchers used the two-average similarity test (t-test) at a significance level of 95% or α = 0.05. From the results of the study, it can be concluded that: (1) The TGT-type cooperative learning model has a significant influence on students' social skills in learning to play futsal, and (2)  The cooperative learning model has a significant influence on students' futsal playing skills.